THE influence of customer reviews, product innovation and digital advertising on purchasing decisions for noodles: influence of customer reviews, product innovation and digital advertising on purchasing decisions for noodles - indayani, lilik; Al Machfudz, Al Machfudz (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
This study aims to analyze the influence of customer reviews, product innovation, and digital advertising on consumer purchasing decisions on Mie Setan products. In today’s digital era, purchasing decisions are not only influenced by product quality, but also by perceptions formed from customer reviews, product updates offered, and the effectiveness of digital promotions. The research method used is quantitative with a survey approach by distributing questionnaires to 150 respondents who are noodles consumers in Pasuruan City. The data analysis technique uses multiple linear regression to test the simultaneous and partial effects of the three independent variables on purchasing decisions. The results of the study indicate that customer reviews, product innovation, and digital advertising simultaneously have a significant effect on purchasing decisions. Partially, customer reviews and product innovation have a positive and significant effect, while digital advertising shows a positive but insignificant effect. These findings indicate the importance of building trust through positive customer reviews and continuing to innovate products to increase consumer purchasing interest.